Q: What is x2 minus 6x plus 5 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

The centre is (3,-1) and the radius is sqrt(10).

one

(3, -21)

Related questions

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

The centre is (3,-1) and the radius is sqrt(10).

x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3

(x - 4)(x - 2)

one

(3, -21)

y â‰¥ 11

x2 + 6x - 2 = 0 x2 + 6x + 9 = 13 (x + 3)2 = 13 x + 3 = ± √13 x = -3 ± √13

y = x2 - 6x + 2 y = x2 - 6x + 9 - 7 y = (x - 3)2 - 7

16 + 6x - x2 = 16 + 8x - 2x - x2 = 8*(2 + x) - x*(2 + x) = (8 - x)*(2 + x)